DIGITALISASI PENDIDIKAN LUAR BIASA DI MASA PANDEMI COVID-19: STUDI KASUS SLB NEGERI 1 PALANGKA RAYA - Muhammad Ishaac (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2021)
The COVID-19 pandemic has resulted the learning in Sekolah Luar Biasa Negeri 1 Palangkaraya doing distance and online in the form of digital learning. It is interesting for researchers to know the steps of digitizing education at the Sekolah Luar Biasa Negeri 1 Palangkaraya, which is known as an Special School based on an integrated curriculum of technology and international standards. This study uses a qualitative approach with descriptive data analysis methods by Miles and Hubberman. The subjects of this study were teachers and parents of students with special needs at the State Special School 1 Palangkaraya. The results of this study indicate that the process of digitalizing education at the Sekolah Luar Biasa Negeri 1 Palangkaraya in the implementation of digitalizing its learning has implemented the 4 principles of digital learning set by Kemendikbud RI, namely education in the context of providing meaningful experiences, focused on life skills, varying considering facilities, and providing appropriate feedback. useful for students, with 3 complex factors that hinder its implementation, namely the factor of children with special needs, parental factors, and environmental factors with various digitalization steps that are variants by each class teacher in accordance with the 4 principles of digital learning.